Childhood morbidity and adulthood ill health. Issue 1 (March 1990) - Power, C; Peckham, C
Abstract : STUDY OBJECTIVE--The aim of the study was to investigate the relationship between the state of health in childhood and ill health in early adult life. DESIGN--The study used data collected as part of the National Child Development Study and related health at 7 years of age to that at 23. A wide range of information on child health in the cohort was available, which was used to construct a broader measure of health status than selected diagnostic categories. SETTING--The survey population was nationwide. PARTICIPANTS--The study population included all children born in the week 3-9 March 1958. They were followed up at 7, 11, 16, and 23 years. Of the target population of 17, 733 births, 12, 537 (76%) were retraced and interviewed at 23. MEASUREMENTS AND MAIN RESULTS--Children at age 7 were allocated to 13 morbidity groups; 20% of children had reported no ill-health apart from the common infectious diseases, but 10% were included in four or more of the morbidity groups. Children with no reported morbidity retained their health advantage into early adulthood: ratios of observed to expected ill health for four of the five indices examined at age 23 were all significantly below one (self rated health 0.81, asthma and/or wheezy bronchitis 0.63, allergies 0.79, emotional health 0.75). Children with more morbidity at age 7 had higher ratios of ill health in adulthood. A chronic condition in childhood was associated not only with excess morbidity in the short term but also with a poor health rating in early adult life (ratio = 1.38). Morbidity was significantly increased for most of the adulthood indices among children with asthma and/or wheezy bronchitis. However most ill health in young adulthood occurred in study members with a relatively healthy childhood. CONCLUSIONS--Although the state of health in childhood has long term implications, it does not form a substantial contribution to ill health in early adult life.